Financing an Income Generating Activities Among the Low Income Urban Households: Malaysian Experience - Omar, Mohamed Zaini; Mohamad Nor, Che Supian; Main Rindam, Main Rindam (Universiti Sains Malaysia, 2012)
This paper aims to provide an insights on the economic performance ofthe Amanah Ikhtiar Malaysia (AIM) Urban Microfinance Programme based on a case study in Georgetown, Penang. The central focus ofthe Urban Microfinance Programme is the provision of loan to the low income urban households to be used for financing an income generating activities. In this connection the purpose of this paper is to examine to (i) what extent the Urban Microfinance Programme has been effective in increasing the incomes ofits participants and (ii) identify what are the factors that have been contributing towards the increment ofthe household incomes. AIM had adopted the Grameen Bank (GB) concept ofmicrofinance and after sucessfully serving the rural area in Malaysia for more than two decades with the initial Rural Microfinance Programme since 1987, had ventured into the urban area in early 2008 with the Urban Microfinance Programme to cater to the poor households and low income groups in the urban area. Thus this programme can be seen as the mechanism of lifting the income ofthe low income urban households.